Research on the Determination Technology of Key Position of Sealing Holes for Gas Extraction Drilling in Zhangcun Coal Mine. (29th April 2022) - Li, Yaobin; Dong, Huanhuan; Guo, Xin
Abstract : In view of the problem of how to determine the position of the sealing hole and increase the concentration of gas extraction, this article proposes the use of a high-pressure gas attenuation method to test the key sealing position and the comparison test of the sealing method using the new sealing position and the traditional sealing position, proposes a method to determine the range of the coal seam roadway loosening belt by measuring the pressure attenuation, and develops a set of devices for rapid determination of the range of the loose belt. Through the field test in Zhangcun Coal Mine, it is shown that when the sealing range is 7.5 m∼18 m, the best effect can be achieved, and when the sealing length is greater than the loose belt, the extraction concentration is higher, and the concentration attenuation and long drilling life are long.